Coordination of the Multiple Witnessing? Variations of the Narrative in the Supplications to the Holy Penitentiary - Marinković, Ana (2010)
The paper is examining the multiple narrations in the supplications to the Holy Penitentiary (published in RPG), and the way in which they reveal the complex mechanisms of the Penitentiary administration, as well as the strategies laying behind the act of turning to the Penitentiary.
ENG